Agricultural Innovation Funds - Rajalahti, Riikka (Washington, DC: World Bank, 2012)
In order for agricultural development to fulfill its potential role as a source of growth and reducer of poverty, it must be constantly renewed through knowledge and innovation. Getting resources into the hands of innovators and providing incentives for producers, agricultural service providers, and entrepreneurs to collaborate in developing and applying new methods and technologies is a priority among institutions concerned with agricultural knowledge. While grants have long been used to finance agricultural innovation, in many countries there has been a shift away from block grant funding and towards the use of innovation funds. These are used to provide incentives and resources for investment and collaboration between innovators, producer groups, private entrepreneurs, and public institutions. Innovation funds allocate grants to targeted applicants based on a system for evaluating the eligibility, relevance, and quality of applicants' proposals.